Please help me with this question.
![Please help me with this question class=](https://us-static.z-dn.net/files/dab/f0aaa59b0e9f4bc4a2780f11e774d089.jpg)
Answer:
y = 6
Step-by-step explanation:
if the triangles are congruent then the corresponding sides are equal.
so
4x + 1 = 13
4x = 13 -1
4x = 12
Therefore x = 3
Now
8x - 2y = 2x + y
y + 2y = 8x - 2x
3y = 6x
3y = 6 * 3
3y =18
Therefore y = 6
Answer:
y = 6
Step-by-step explanation:
Since the triangles are congruent then corresponding sides are congruent
4x + 1 = 13 ( hypotenuse are congruent )
Subtract 1 from both sides
4x = 12 ( divide both sides by 4 )
x = 3
Thus
8x - 2y = 2x + y ( substitute x = 3 )
8(3) - 2y = 2(3) + y, that is
24 - 2y = 6 + y ( subtract y from both sides )
24 - 3y = 6 ( subtract 24 from both sides )
- 3y = - 18 ( divide both sides by - 3 )
y = 6